Förskolan som ensemble: Om metaforer för ökad förståelse av rektors pedagogiska ledarskap. - Erlandsson, Magnus; Riddersporre, Bim; Stier, Jonas (Educare, 2025)
While research on pedagogical leadership usually starts from an ideal idea of what this form of leadership might be, or from governing documents, in this article we add to the understanding of how preschool principals themselves comprehend, practice, and develop their pedagogical leadership. This is done, firstly, by recounting and problematizing how principals position themselves vis-à-vis their organization and employees; secondly, by generating metaphors to capture the essence of preschool principals’ own understanding, enactment, and progress of their pedagogical leadership. The study is based on 78 texts written by preschool principals, texts that each explicitly or implicitly relate to four crucial parts of the principal’s assignment, with special focus on the pedagogical leadership: the principal’s 1) image of the ideal leadership, 2) interpretation of the pedagogical leadership assignment, 3) individual leadership practices, and 4) leadership development. The texts analysis is followed by a metaphorical approach, where metaphors are established and then used to develop the understanding of preschool principals’ pedagogical leadership. We argue that five metaphors can represent the principals’ understanding, enactment, and progress of their pedagogical leadership: firstly, in four subordinate metaphors – sing-along leader, conductor, dissonance, and jam session – secondly, in an over-arching metaphorical concept: the ensemble.